An Ethnobotanical Study on the Farming System of the Makian Ethnic Group in Halmahera Island, North Maluku - Muhamad Nikmatullah; Mulyati Rahayu; Siti Susiarti; Marwan Setiawan; Ida Farida Hasanah (The Ethnobiological Society of Indonesia, 2021)
Farming is an activity carried out by humans to utilize biological resources, especially for producing food. Bale Village, Oba District, Tidore, Halmahera Island, North Maluku is inhabited by the Makian ethnic group, originating from Makian Island. They are local transmigrants. In this study, researchers conducted direct observation and interviews with key informants who had expertise and information in agriculture at the research location. The results showed that the farming is carried out in yards (kintal) and fields (doba). The agricultural pattern implemented by the Makian people is still traditional. They still use simple technology. Coconut, nutmeg, cocoa, and coffee are the Makian people’s main commodities. The local wisdom that is still practiced by them is planting and harvesting their agricultural products according to the customs of their ancestors. They also do not sell their agricultural land to outsiders.